2016
DOI: 10.1186/s12981-016-0100-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with HIV viral load “blips” and the relationship between self-reported adherence and efavirenz blood levels on blip occurrence: a case–control study

Abstract: BackgroundThe uncertain etiology of HIV viral load (VL) blips may lead to increased use of clinical resources. We evaluated the association of self-reported adherence (SRA) and antiretroviral (ART) drug levels on blip occurrence in US Military HIV Natural History Study (NHS) participants who initiated the single-tablet regimen efavirenz/emtricitabine/tenofovir disoproxil fumarate (EFV/FTC/TDF).MethodsART-naïve NHS participants started on EFV/FTC/TDF between 2006 and 2013 who achieved VL suppression (<50 copies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…In contrast to previous studies, we focused only on the factors of high-risk LLV subgroup leading to VF, to identify conditions that need prompt treatment during ART. Although we used new definitions of LLV and VF, we found some similar risk factors as several resource-rich cohort studies, including the high zenith VL and low nadir CD4 + T cell counts [3,22,23]. In addition, we found that long-term ART, AZT + 3TC + NVP or DDI + NRTI+NNRTI regimens, Manchu and subtype B′ infection were all risk factors in this study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In contrast to previous studies, we focused only on the factors of high-risk LLV subgroup leading to VF, to identify conditions that need prompt treatment during ART. Although we used new definitions of LLV and VF, we found some similar risk factors as several resource-rich cohort studies, including the high zenith VL and low nadir CD4 + T cell counts [3,22,23]. In addition, we found that long-term ART, AZT + 3TC + NVP or DDI + NRTI+NNRTI regimens, Manchu and subtype B′ infection were all risk factors in this study.…”
Section: Discussionsupporting
confidence: 77%
“…Although most studies suggest that LLV contributes to VF, the potential risk factors of LLV have not been sufficiently investigated. Several HIV cohort studies from developed countries where subtype B was predominant found that the high zenith baseline VL and low nadir baseline CD4 + T cell counts were associated with the risk of LLV [3,[22][23][24][25]. However, the evidence from non-subtype B infected cases and resource-limited regions are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This study found a significantly higher incidence of viral blips among children compared to adults. The reported incidence of blips varies in different populations (Farmer et al, 2016;Grennan et al, 2012;Havlir et al, 2001;Kanapathipillai et al, 2014;Sorstedt et al, 2016), largely due to different definitions and variability of the assays for VL. We used a common definition of viral blip, as a single VL measurement !50 copies/ml preceded and followed by VL <50 copies/ml (Fung et al, 2012;Ryscavage et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A proportion of individuals on ART experience low-level viraemia (LLV) and/or transient viraemia; for example, viral blips have been reported in up to 40% of HIV-positive individuals on ART (Grennan et al, 2012;Havlir et al, 2001;Sorstedt et al, 2016). Viral blips have been shown to be associated with higher HIV pretreatment VL and lower CD4 count at the time of ART initiation (Farmer et al, 2016;Havlir et al, 2001;Sorstedt et al, 2016). There is some evidence that they may impair CD4 cell recovery and maintain ongoing low-grade immune activation (Taiwo et al, 2013;Zoufaly et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Other explanations could be stochastic variations [ 8 ], conditions that temporarily could lead to increased HIV replication such as infections [ 9 ] or vaccinations [ 10 12 ], and low drug concentrations in blood because of poor adherence or poor absorption of antiretroviral drugs. Prior studies have reported blip incidence between 13 and 40 % [ 13 16 ]. The large differences are due to different blip definitions and viral load assays.…”
Section: Introductionmentioning
confidence: 99%